The role of experimental avoidance, emotional regulation difficulties, and body image concern in predicting the probability of suicide among adolescent girls - Hosna Vafapoor; Jahangir Karami; Khodamorad Momeni (روانشناسی و روانپزشکی شناخت, 2021)
Introduction: Suicide is one of the mental health problems and the third leading cause of death among adolescents. Aim: This study aimed to investigate the role of experimental avoidance, emotional regulation difficulties, and body image concern in predicting the probability of suicide among adolescent girls. Method: The method of the present study was descriptive of the type of correlation and the statistical population included all adolescent girls in Kermanshah City in 2019. By available sampling method and based on Morgan table, 350 people were selected as a sample. The research instruments included the adolescents Suicide Questionnaire, the Bond et al. Experimental Avoidance Questionnaire, the Grater and Roemer Emotional Regulation Difficulties Scale, and the Lillton body image concern questionnaire, all of which were valid and reliable. To analyze the data, Pearson correlation and multivariate regression analysis were used simultaneously, which were finally analyzed by SPSS software version 22. Results: The results showed that experimental avoidance, emotional regulation difficulties components (except lack of emotional awareness), and body image concern had a significant effect on the probability of suicide (P>0.001). The results of the analysis also showed that the predictor variables together can accurately determine the 27.7% the probability of suicide. Conclusion: The probability of suicide in adolescent girls can be predicted by the variables of experimental avoidance, emotional regulation difficulties, and body image concern. Therefore, it is suggested that psychologists and counselors pay attention to the role of experimental avoidance, emotional regulation difficulties, and body image concern to reduce adolescent's suicide.